2018
DOI: 10.3897/compcytogen.v12i1.22344
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional chromosome painting in Synallaxis frontalis (Passeriformes, Furnariidae) reveals high chromosomal reorganization, involving fissions and inversions

Abstract: In this work we performed comparative chromosome painting using probes from Gallus gallus (GGA) Linnaeus, 1758 and Leucopternis albicollis (LAL) Latham, 1790 in Synallaxis frontalis Pelzeln, 1859 (Passeriformes, Furnariidae), an exclusively Neotropical species, in order to analyze whether the complex pattern of intrachromosomal rearrangements (paracentric and pericentric inversions) proposed for Oscines and Suboscines is shared with more basal species. S. frontalis has 82 chromosomes, similar to most Avian spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…In addition, for better knowledge of the Common quail genome, Fluorescence In Situ Hybridization ( FISH ) will be performed for individual microchromosome identification ( Lithgow et al 2014 , McPherson et al 2014 ). Though specific FISH probes of GGA11-28 chicken lampbrush microchromosomes can be used for the 10 smallest chicken microchromosomes, GGA29-38, no individual molecular tags have been established to date ( Galkina et al 2017 , Kretschmer et al 2018 ). Also, the characterization of the nuclear genetic markers (microsatellites) allowed to distinguish both taxa of the quail and their hybrids, and to estimate the genetic introgression ( Boecklen and Howard 1997 , Puigcerver et al 2000 , Rodríguez-Teijeiro et al 2003 , Barilani et al 2005 , Vähä and Primmer 2006 , Chazara et al 2006 , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for better knowledge of the Common quail genome, Fluorescence In Situ Hybridization ( FISH ) will be performed for individual microchromosome identification ( Lithgow et al 2014 , McPherson et al 2014 ). Though specific FISH probes of GGA11-28 chicken lampbrush microchromosomes can be used for the 10 smallest chicken microchromosomes, GGA29-38, no individual molecular tags have been established to date ( Galkina et al 2017 , Kretschmer et al 2018 ). Also, the characterization of the nuclear genetic markers (microsatellites) allowed to distinguish both taxa of the quail and their hybrids, and to estimate the genetic introgression ( Boecklen and Howard 1997 , Puigcerver et al 2000 , Rodríguez-Teijeiro et al 2003 , Barilani et al 2005 , Vähä and Primmer 2006 , Chazara et al 2006 , 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Birds have experienced fast series of speciation events during millions of years ( Nadachowska-Brzyska et al 2015 , Griffin et al 2015 ). Although intra-chromosomal rearrangements occur widely, inter-chromosomal ones are rare events estimated as 1.25 per million years ( Zhao and Bourque 2009 , Zhang et al 2014 , Hooper and Price 2017 , Kretschmer et al 2018 ). These reshufflings could be the cause or consequence of speciation, or a result of adaptation ( Nishida et al 2008 , Völker et al 2010 , Romanov et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of high number of near-undistinguishable microchromosomes, most bird karyotypes are partial and confined to a few macrochromosomes ( Shibusawa et al 2004 ). However, the use of chicken probes has allowed identification of several microchromosomes in some bird species ( Fillon et al 1998 , Nie et al 2015 , Galkina et al 2017 , Kretschmer et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the fission of GGA2, into two chromosomes in C. lineata (CLI1 and CLI5q) (Figure 3), is atypical for Passeriformes; normally GGA2 is conserved and corresponds to the largest pair (Table 1) (Kretschmer et al, 2014(Kretschmer et al, , 2015Santos et al, 2017). Moreover, the centric fission of GGA2 was observed in other Suboscines species, belonging to parvorder Furnariida -Synallaxis frontalis (Kretschmer et al, 2018b) and Glyphorynchus spirurus (Ribas et al, 2018) 2…”
mentioning
confidence: 96%
“…Of the twenty species of this order examined by molecular genetics so far, six belong to the Suborder Suboscines: Elaenia spectabilis, Pitangus sulphuratus, Serpophaga subcristata and Satrapa icterophrys (Tyrannida -Tyrannidae), Synallaxis frontalis and Glyphorynchus spirurus (Furnariida -Furnariidae) (Guttenbach et al, 2003;Derjusheva et al, 2004;Itoh and Arnold, 2005;Kretschmer et al, 2015;Santos et al, 2017;Rodrigues et al, 2017;Kretschmer et al, 2018b;Ribas et al, 2018). Using as reference the putative ancestral karyotype of birds (Griffin et al, 2007), all species analyzed by chromosome painting with Gallus gallus probes (GGA) have presented conservation of ancestral macrochromosomes, except for ancestral pair 1which corresponds to two pairs representing a synapomorphy for Passeriformes -and pair 2, which has undergone fission in Satrapa icterophrys (Parvorder Tyrannida), Synallaxis frontalis and Glyphorynchus spirurus (Parvorder Furnariida) (Rodrigues et al, 2017;Kretschmer et al, 2018b;Ribas et al, 2018). Additionally, the use of 18S rDNA probes has revealed that the number and distribution of NORs varies from 1-3 pairs in Passeriformes (Kretschmer et al, 2014(Kretschmer et al, , 2015Rodrigues et al, 2017).…”
mentioning
confidence: 99%